Pengembangan Alat Ukur Komitmen Organisasi - Tri Muji Ingarianti (Universitas Negeri Padang, 2015)
Abstract: Development of a measuring instruments organizational commitment. This study aimed to develop and to test validity and reliability of measuring instruments organizational commitment. Subject were 515 employees. The results of analysis validity of each item when compared to the overall score scale produce very significant data on 0.01 level, means scale of these organizational commitment is valid to uncover the organization's commitment and its aspects. Based on analysis known reliability coefficient of each aspect indicates a value above 0.6 is 0.803 to 0.897, which means that every aspect of the organization's commitment to scale reliably. Similarly, the reliability scale organizational commitment showed a value of 0.938, it can be concluded that this scale of the organizational commitment is reliable.Keywords: organizational commitment, validity, reliabilityAbstrak: Pengembangan alat ukur komitmen organisasi. Penelitian ini bertujuan untuk menyusun dan melakukan uji validitas dan reliabilitas alat ukur komitmen organisasi. Subjek penelitian adalah 515 karyawan. Hasil analisis validitas setiap item jika dibandingkan dengan skor keseluruhan skala menghasilkan data yang sangat signifikan pada taraf level 0,01 dengan kata lain skala komitmen organisasi ini valid untuk mengungkap komitmen organisasi dan aspek-aspeknya. Berdasarkan hasil analisa diketahui koefisien reliabilitas masing-masing aspek menunjukkan nilai diatas 0,6 yaitu 0,803-0,897 yang berarti bahwa setiap aspek dalam skala komitmen organisasi ini reliabel. Begitu pula dengan reliabilitas skala komitmen organisasi menunjukkan nilai sebesar 0,938 maka dapat disimpulkan bahwa skala komitmen organisasi ini reliabel.Kata kunci: komitmen organisasi, validitas, reliabilitas